Chemical Composition and Antioxidant Activity of Aloe vera from the Pica Oasis (Tarapacá, Chile) by UHPLC-Q/Orbitrap/MS/MS - Cristina Quispe; Michael Villalobos; Jorge Bórquez; Mario Simirgiotis (Journal of Chemistry)
The chemical composition of Aloe vera growing in the small town of San Andrés de Pica, an oasis of warm waters and typical fruits, located in Tamarugal province in the Northern Chilean region of Tarapacá is reported. The chemical characterization was performed using liquid chromatography (UHPLC) coupled to PDA and high-resolution mass spectrometry (HESI-Q-Orbitrap®-MS) in four different plant parts of Aloe (peel, flowers, gel, and roots). Twenty-five phenolic compounds were identified, including cinnamic acids and other derivatives (e.g., caffeic and chlorogenic acids), chromones (e.g., aloesin and isoaloeresin D), anthracene compounds and derivatives (e.g., aloin A/B and emodin), and several C-flavonoids (e.g., orientin and isovitexin), among others. Total antioxidant activity of the ethanolic extracts of the peels, flowers, gel, and roots was measured as the capturing of the DPPH• and ABTS•+ radicals, while the iron-reducing antioxidant power (FRAP) was measured by spectroscopic methods. The peel had the highest antioxidant activity with values of 2.43 mM ET/g MF (DPPH•), 34.32 mM ET/g MF (ABTS•+), and 3.82 mM ET/g MF (FRAP). According to our results, the peel is the best part of the plant for the production of nutraceuticals or cosmetics products for its greatest number of bioactive compounds. This is a new and innovative finding since the only part used in traditional medicine is the gel of Aloe, and the peel is generally considered waste and discarded.